2013
DOI: 10.1111/iej.12043
|View full text |Cite
|
Sign up to set email alerts
|

CpG ODN‐induced matrix metalloproteinase‐13 expression is mediated via activation of the ERK and NF‐κB signalling pathways in odontoblast cells

Abstract: The CpG ODN-induced MMP-13 expression in OLCs is mediated through TLR9, NF-κB and the ERK pathway indicating that potentially the recognition of CpG ODN by TLR9 on odontoblasts may regulate the remodelling of injured dental pulp and hard tissues by inducing MMP-13 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Moreover, we found a reduction of all analysed activation parameters induced by PPVO after inhibiting JNK signalling with SP600125 (Figure 4B). The JNK signalling cascade is known to be involved in the induction of pro-inflammatory cytokines by TLR [29], but the JNK inhibitor SP600125 only marginally influences CpG-ODN-induced matrixmetalloproteinase 13 production by odontoblasts or RANTES secretion by Langerhans cells [38], [39]. We demonstrate that SP600125 inhibits PPVO-mediated type I IFN induction by TLR9 in pDC.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, we found a reduction of all analysed activation parameters induced by PPVO after inhibiting JNK signalling with SP600125 (Figure 4B). The JNK signalling cascade is known to be involved in the induction of pro-inflammatory cytokines by TLR [29], but the JNK inhibitor SP600125 only marginally influences CpG-ODN-induced matrixmetalloproteinase 13 production by odontoblasts or RANTES secretion by Langerhans cells [38], [39]. We demonstrate that SP600125 inhibits PPVO-mediated type I IFN induction by TLR9 in pDC.…”
Section: Discussionmentioning
confidence: 74%
“…TLR9 recognizes unmethylated CpG motifs, and then induces the recruitment of MyD88 to initiate downstream signaling (Takeshita et al, 2004). Furthermore, it has been shown that TLR9 associates with MyD88 to initiate CpG ODN mediated effects via signal-transducing pathways including NF-κB, p38 MAPK, JNK, AP-1, and ATF-2 (Akira et al, 2001; Osawa et al, 2006; Zhang et al, 2013). PBMCs express a wide range of TLRs and are crucial targets for various pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…All the the mitogen-activated protein kinase (MAPK) pathways (ERK1/2, p38, and JNK) have been shown to be involved in MMP-13 expression in response to various stimuli and stress (Nakai et al, 2012; Onodera et al, 2002; Rossa et al, 2007; Zhang et al, 2012). However, the MAPK pathways which are critical in the LPS-induced MMP-13 gene regulation remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…MMP-13 expression can be regulated by MAPK in response to various stimuli and in different cells (Nakai et al, 2012; Onodera et al, 2002; Rossa et al, 2007; Zhang et al, 2012). However, how SOCS3 regulates MAPK in osteoblast is not known.…”
Section: Discussionmentioning
confidence: 99%